The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2807/1560-7917.es.2022.27.14.2100503
|View full text |Cite
|
Sign up to set email alerts
|

HIV, STI and renal function testing frequency and STI history among current users of self-funded HIV pre-exposure prophylaxis, a cross-sectional study, Germany, 2018 and 2019

Abstract: Introduction Users of pre-exposure prophylaxis (PrEP) require periodic testing for HIV, sexually transmitted infections (STI) and renal function. Before PrEP was made free of charge through statutory health insurance in late 2019, PrEP users in Germany had to pay for testing themselves. Aim We investigated self-reported HIV, STI and renal function testing frequencies among self-funded PrEP users in Germany, factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In a survey of PrEP users among men who have sex with men in Germany, 59.2% of users were tested for HIV every 3 months or more often, compared with 40.8% in our study. 10 An even higher estimate was reported by Tassi et al among PrEP users in France. Using a historical cohort from the French national health database, 86.3% of users were tested for HIV within 1 month after initiation, 11 suggesting significant room for improvement in the U.S.…”
Section: Discussionmentioning
confidence: 85%
“…In a survey of PrEP users among men who have sex with men in Germany, 59.2% of users were tested for HIV every 3 months or more often, compared with 40.8% in our study. 10 An even higher estimate was reported by Tassi et al among PrEP users in France. Using a historical cohort from the French national health database, 86.3% of users were tested for HIV within 1 month after initiation, 11 suggesting significant room for improvement in the U.S.…”
Section: Discussionmentioning
confidence: 85%
“…In a study from France comparison of HIV negative PrEP users, HIV negative PrEP non-users and people living with HIV (PLWH) suggested that the overall STI incidence was significantly higher among HIV negative PrEP non-users compared to PLWH, with no difference between PLWH and PrEP users. 53 Another study from Germany reported no association between PrEP use and STI rates. 54 Similarly, adherence to PrEP was not associated with STI rates in a report from the US.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, people who use PrEP intermittently may be less likely to screen frequently for STIs as they may not attend PrEP services on a regular basis. Out-of-pocket costs for increased frequency of STI screening and treatment or transportation when the frequency of screening is shorter than the PrEP follow-up visits [33] can add to the challenges of frequent screening [34] . Interviews from a younger group of people who would benefit from PrEP also indicated that participants were unwilling to be screened every 3 months due to perceptions that follow-ups would be time-consuming and inconvenient [35] .…”
Section: Discussionmentioning
confidence: 99%